Can Body Mass Index Predict Metformin Failure in Women with Gestational Diabetes? [38I]. (May 2018) - Persad, Malini D.; Ou, Jennie; Bernasko, James; Garry, David; Garretto, Diana; Herrera, Kimberly
Abstract : INTRODUCTION: To determine if pre-pregnancy body mass index (BMI) predicts metformin failure in the treatment of women with gestational diabetes (GDM). METHODS: A retrospective cohort study of women with GDM was conducted from 2013-2016. Included in the study were women with GDM started on metformin after a failed trial of diet therapy. Excluded from the study were women with pre-existing diabetes mellitus or initiated glyburide or insulin therapy. Women were categorized as having adequate glycemic control on metformin (metformin success) or requiring the addition of or transition to an insulin regimen (metformin failure). Metformin failure was defined as the inability to obtain glycemic control despite utilization of the maximum metformin dosage or provider discretion. Maternal characteristics and BMI were collected from the hospital's electronic medical record and compared between groups. Parametric and nonparametric statistical analyses were performed with a p value of < 0.05 as significant. The sensitivity and the specificity of BMI as a screening test for metformin failure were analyzed and the corresponding ROC curve was plotted to assess the performance of the test. RESULTS: A total of 139 women with gestational diabetes were identified, of which 21 (15%) failed metformin therapy. There were no differences in maternal demographics, BMI and BMI classifications between groups. The ROC curve revealed an optimal cut-off BMI to predict metformin failure of 38.7kg/m 2 with a sensitivity 38.1 % and specificity 81.4% (AUC 0.56, p=0.236). CONCLUSION: Pre-pregnancy BMI may have limited utility in predicting metformin failure.